Associations of the C-reactive protein-albumin-lymphocyte index with all-cause and cardiovascular mortality among individuals with cardiovascular disease: evidence from the NHANES 2001–2010 - Dunzheng Han; Lanlan Wu; Haobin Zhou; Yuting Xue; Shangfei He; Zhuang Ma; Shuwen Su; Peixin Li; Shenrong Liu; Zheng Huang (BMC Cardiovascular Disorders)
Abstract Background Evidence regarding the C-reactive protein‒albumin‒lymphocyte (CALLY) index and mortality risk in individuals with cardiovascular disease (CVD) is scarce. This study investigated the relationships of the CALLY index with all-cause and cardiovascular mortality risk in CVD patients among American adults. Methods This study enrolled 2183 CVD individuals from five NHANES cycles (2001–2010), and mortality outcomes were determined by linking the data to National Death Index (NDI) records up to December 31, 2019. Weighted multivariate Cox regression models and subgroup analyses were performed to assess the associations of the CALLY index with all-cause and cardiovascular mortality. A restricted cubic spline (RCS) was used to visualize the association of the CALLY index with mortality risk. Results During a median follow-up of 122 months (interquartile range, 71–157 months), 1208 (weighted percentage, 49.62%) of the 2183 CVD individuals died, including 398 (weighted percentage, 24.85%) with cardiovascular deaths and 810 (weighted percentage, 75.15%) with noncardiovascular deaths. Cox regression revealed an inverse correlation between the CALLY index and the risk of all-cause and cardiovascular mortality after adjusting for covariates. Compared with individuals with a lower CALLY index, those with a higher CALLY index had a significantly lower risk of both all-cause (HR 0.58, 95% CI: 0.48, 0.71, p < 0.001) and cardiovascular mortality (HR 0.54, 95% CI: 0.38, 0.76, p < 0.001). The RCS regression analysis revealed a nonlinear association between the CALLY index and all-cause and cardiovascular mortality (p < 0.05 for nonlinearity) in CVD patients. The associations were consistent in the subgroup analyses regardless of age, sex, income, education level, race, smoking status, diabetes, and hypertension (all p values for interactions > 0.05). Conclusion An increased CALLY index is independently associated with decreased all-cause and cardiovascular mortality in CVD patients.